Patient depression and caregiver attitudes: Results from The AgeD in HOme Care study - Soldato, Manuel; Liperoti, Rosa; Landi, Francesco; Carpenter, Iain G.; Bernabei, Roberto; Onder, Graziano (Journal of affective disorders, 2008)
The present cross-sectional study was aimed to evaluate the association between care recipient depression and caregiver attitudes. Data were from The AgeD in HOme Care project, a study enrolling subjects aged ≥ 65 years receiving home care in Europe. Depression was diagnosed as a score ≥ 3 on the MDS Depression Rating Scale. Caregiver attitudes were assessed using two measures: 1) caregiver dissatisfaction (the caregiver was dissatisfied with the support received from family and friends); and 2) caregiver distress (the caregiver expressed feelings of distress, anger, or depression). Mean age of 3415 participants was 82.4 years, 2503 (73.3%) were women and 430 (12.6%) were depressed. Dissatisfaction was significantly more common among caregivers of depressed, compared with those of non depressed patients (32/430, 7.4% vs. 78/2985, 2.6%; p = < 0.001). After adjusting for potential confounders, patient depression was still significantly associated with caregiver dissatisfaction (OR: 1.84; 95% CI: 1.12–3.03). Similarly, distress was significantly more common among caregivers of depressed patients, compared with those of non depressed patients (81/430, 18.8% vs. 175/2985, 5.9%; p < 0.001). After adjusting for potential confounders, patient depression was still significantly associated with caregiver distress (OR: 2.41; 95% CI: 1.72–3.39). The cross-sectional design of the study cannot provide the cause–effect relationship between depression and caregiver attitude; no data were collected on caregiver characteristics. Among older adults depression is associated with increased caregiver dissatisfaction and distress. Knowledge of factors influencing caregiver attitudes may be valuable to study interventions aimed to promote patient and caregiver well being.